An empirical inquiry into the distributional consequences of energy price shocks - Luca Eduardo Fierro; Mario Martinoli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
We estimate how energy shocks affect the functional distribution of income. Using structural vector autoregressions identified with the oil supply news instrument proposed by Kanzig (2021), we find that an increase in oil prices leads to a substantial and long-lasting decline in the wage share. Real aggregate wage income is significantly impacted, with a considerable part of this decline stemming from distributive dynamics. We also investigate possible asymmetries in the response to oil supply shocks, finding that the wage share is more sensitive to negative shocks than to positive ones. This suggests that wage earners lose from oil price hikes more than they benefit from declines.
Keywords: C32; E25; E31; E32; Q43; 330; Oil shocks; Income distribution; proxy-SVAR; Asymmetries